Combination of 2,4-D and stress improves indirect Somatic Embryogenesis in Cattleya maxima Lindl - Cueva Agila, A. (2013)
Many members of the Orchidaceae, the largest vascular plant family in Ecuador, are at risk of extinction. It was therefore considered important to establish an efficient way of clonal propagation based on somatic embryogenesis of Cattleya maxima, a native Ecuadorian orchid. To this end, we evaluated the effect on somatic embryo induction of twelve combinations of 2,4-dichlorophenoxyacetic acid (2,4-D) and Thidiazuron (TDZ), as well as three kind of stresses. Protocorms produced 42% of embryogenic calli on Murashige and Skoog (MS) medium, compared to 96,3% when protocorms were stressed for 6 hours with 0,3M NaCl, followed by cultivation on MS medium supplemented with 0,1 mg L? 1 2,4-D. Our data demonstrated that the combination of either salt (0,3M NaCl) or osmotic stress (0,4M sorbitol) with subculture on 2,4-D (0,1 mg L? 1) medium significantly increases the percentage of protocorms with embryogenic callus. The number of embryos per embryogenic callus was not significantly different from that obtained after subculture in growth factor-free medium.